THE IMAGE OF SOCIO-ECONOMIC LIFE OF THE POPULATION IN MUQIMI’S ORIGINAL WORKS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article is devoted to the images of socio-economic life in the life and works of Muhammad Aminkhoja Muqimi, one of the great Uzbek poets. The socio-economic aspects of the events that happened in the life of the population at the end of the 19th century and the beginning of the 20th century are covered in detail. In addition, the principles of this great poet are still present today and exist among the population.